Economics of organic and conventional pepper production in Idukki district - Sneha Elizabeth Varghese (Department of Agricultural Economics, College of Agriculture, 2012)
The research entitled “economics of organic and conventional pepper production in Idukki district” was done in Azutha and Kattapana blocks of Idukki district. The study was undertaken with the objective to study the economics of organic and conventional pepper production, resource use efficiency, adoption of practices, marketing system and constraints in production and marketing of pepper. In this study the cost of cultivation was worked out using the A B C cost concepts. Since pepper is perennial crop, cost of production was studied by considering establishment cost (cost during pre bearing period). The establishment cost was amortized by multiplying it with annuity and an annualized establishment cost was obtained. This cost was added to the maintenance cost to obtain the total cost. Cost of production was worked out considering both rental value of owned land and market rent for leased in land. Allocative efficiency of the resource was estimated using Cobb – Douglas production function. Extent of adoption of recommended practices by organic and conventional pepper growers were analysed. Marketing channel of both organic and conventional pepper was identified and price spread was calculated for organic and conventional marketing channel. For organic pepper cost A was worked out to Rs 82,192 of which hired labour accounted to about 54 per cent, followed by cost of manures (28 per cent). Cost B1, B2, C1, C2 and C3were respectively Rs 83,062, Rs 4,84,420, Rs 1,29,879, Rs 5,31,237 and Rs 5,84,361. For conventional pepper out of Rs 77,230 estimated as cost A, hired labour was again the highest contributor accounting to 62 per cent and cost of manure and fertilizers occupied the second position accounting to 19 per cent of cost A. Cost B1, B2, C1, C2 and C3 were respectively Rs 77,900, Rs 4,70,091, Rs 1,18,910, Rs 5,11,102 and Rs 5,62,212. The gross returns obtained by organic farmers was Rs 3, 41,576 per ha which was 5.26 per cent lower than the conventional system (Rs 3,59,544 per ha). B – C ratio with respect to cost A was as high as 4.16 and 4.66 for organic and conventional farmer. The cost of production worked out to Rs 649 and Rs 572 per kg for organic and conventional pepper respectively when rental value of land was considered. The cost of production was analyzed considering the market rent for leased in land was found to be Rs 238 and Rs 205 respectively for organic and conventional pepper production. Cobb – Douglas production function was used to study the resource use efficiency of both production systems. From the allocative efficiency analysis it is understood that the inputs used in both organic and conventional pepper production is not optimal and could be increased further. Ten per cent and 22 per cent of the recommended practices were only adopted respectively by conventional and organic pepper growers. Climate, disease and pest attack, labour were identified as the major constraints by both organic and conventional farmers. High variability in price was identified as the major marketing constraint. Single export oriented marketing channel was observed for organic pepper and price spread worked to Rs 232 per kg. Various marketing channels of conventional pepper were observed, but the price spread of the local channel alone was calculated due to the complexity of other channels. The local channel observed for conventional pepper was producer – village trader – local retailer – consumer (tourist) and the price spread estimated was Rs 208 per kg with producer’s share of 64.70 per cent.